Filsafat Kebahagiaan Menurut Al-Kindi dan Al-Farabi - Auliati, Auliati; Hambali, Radea Yuli (Jurnal Riset Agama, 2023)
This study aims to discuss the concept of happiness according to Al-Kindi and Al-Farabi. The method used in this research is descriptive analysis with a qualitative approach. The data collected using library techniques, namely collecting various primary data and secondary data. The primary data used in this study were books written by Al-Kindi and Al-Farabi, while the secondary data in this study are books, scientific articles, documentation, and others related to this research. The result of this study is that there is a very significant difference between the opinions of Al-Kindi and Al-Farabi regarding the philosophy of happiness. For Al-Kindi, happiness is a human effort to implement God's actions in this world. In this way, humans will not rely on happiness on material things. The way that can be done by humans to achieve happiness is with rationality and soul. As for Al-Farabi, happiness is a good thing done by humans who want to be sincere and there is no balance in any form. Humans who get happiness for Al-Farabi are those who have achieved four virtues, namely theoretical virtues, primacy of thinking, moral virtues, and amaliah virtues.